Biblioteca e memória: interlocuções com a comunidade - Silva, Ana Pricila Celedonio da (2018)
It aims to present the perspective of the community library as mediator and diffuser of the collective memory of the community. In this sense, it presents as an empirical study the community libraries Criança Feliz and Sorriso da Criança, located in the city of Fortaleza, Ceará. The objective of the research was to investigate how these libraries have acted as spaces that promote collective memory and are recognized in this way by the residents of the spaces where they are located. According to this objective, investigations were carried out on the main characteristics of the communities, as well as on the activities developed by the libraries and their collections, seeking to ascertain if they refer to an action focused on the diffusion of the local memory and culture. In addition, we sought to identify how the relationship between library and community occurs, and how the actions of the same reverberates in the imaginary of the residents of these places. Setting up a qualitative, exploratory and bibliographic research, topics related to memory, community and library are discussed, observing in each one of them its conceptual, theoretical, historical and contemporary aspects, articulating with them, discussions about the culture, identity, daily life, belonging, among others. Supported by the methodological presuppositions of ethnography and the technique of oral history, the research is characterized as an immersion and interpretation project of the locus where the above mentioned libraries are inserted, in order to contemplate them from the perspective of the community library acting as interlocutor of collective memories. For this purpose, participant observation, focused interviews with managers and the holding of discursive workshops with adults and elderly people were used as methodological resources. From this study, it was possible to identify the cultural and memorial role of these spaces, evidenced in a special way by means of two actions, the Tecendo Memórias project, carried out by the Biblioteca Comunitária Sorriso da Criança, and the Histórias e Quintais project, organized in partnership with the Biblioteca Comunitária Criança Feliz. These projects demonstrated the dialogical and plurality of the community library as a mediator of memories, identities and everyday knowledge.